Tractive performance of 4x4 tyre treads on pure sand. - Eatough, Kieron (Cranfield University, 2002)
This thesis examined the difficulties of generating traction from 4x4 (light truck) tyres in pure sand conditions. Investigations conducted in the Cranfield University Soil Dynamics Laboratory measured the tractive performance of a range of production and prototype 4x4 tyre tread patterns to quantify the effect of tread features upon tractive performance. The investigation also quantified the amount of sand displacement instantaneously occurring beneath the tyre, by a novel application of radio frequency identification (RFID) technology, which determined sand displacements to an accuracy of ±5.5 mm. A limited number of normal contact stress measurements were recorded using a TekScan normal pressure mapping system. This technology was employed in a new manner that allowed pressure distributions to be dynamically recorded on a deformable soil surface. Models were developed or adapted to predict rolling resistance, gross thrust of a tyre and the gross thrust effect due to its tread. Net thrust was predicted from refined versions of equations developed by Bekker to predict gross thrust and rolling resistance. These were modified to account for dynamic tractive conditions. A new tread model proposed by the author produced a numerical representation of the gross thrust capability of a tread based on factors hypothesised to influence traction on loose sand. This allowed the development of a relationship between the features of the tread and its measured gross thrust improvement (relative to a plain tread tyre), from which a total relationship was developed. The tread features were also, in combination with the wheel slip, related to the sand displacements and net thrusts simultaneously achieved. The sand displacement results indicated that the majority of the variation in displacement between the different treads occurred in the longitudinal (rearward) direction. This effect was influenced by the wheel slip, as increased slip caused greater displacements, so the differences between the treads were greater at higher slips. The treads that generated the highest relative displacements also derived the higher gross thrusts (up to +5% extra gross thrust compared to a plain tread), although at the higher slips this also caused increased sinkage. As sinkage increased, the rolling resistance increased at a fester rate then the gross thrust, and thus the net thrust reduced. To prevent this effect the wheel slip should be limited to a maximum of 20% at low forward speeds (approximately 5 km/h). Current market forces dictate that the biggest benefit that tyre manufacturers could offer in desert market regions would be to optimise road-biased tyres to suit loose sand conditions. The modelling developed indicated that this could be achieved by maximising the number of lateral grooves (and thus lateral edges) featured on a tread, however care would have to be exercised so as not to compromise the necessaiy on-road capability. The models could also be used to quantifiably determine from a choice of possible tyre treads, the tread that would offer most traction on pure loose sand.